2012
DOI: 10.1093/treephys/tps080
|View full text |Cite
|
Sign up to set email alerts
|

The MdTFL1 gene of apple (Malus x domestica Borkh.) reduces vegetative growth and generation time

Abstract: TFL1 is known as a floral repressor in Arabidopsis thaliana (L.) Heynh. In apple there are two TFL1 homologs, MdTFL1-1 and MdTFL1-2. The MdTFL1-1 gene was silenced in transgenic clones expressing a hairpin gene construct of a 323 bp fragment of MdTFL1-1. The hairpin gene construct was transferred to three different apple genotypes. Of 22 transgenic clones, 21 showed a significant reduction in MdTFL1-1 mRNA expression. Precocious flowering was obtained for 20 clones, which flowered already during in vitro culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 37 publications
2
73
0
Order By: Relevance
“…Flower initiation has been intensively studied in Arabidopsis, and orthologs/homologs of genes for LFY, AP1, and TFL1 have been cloned from apple trees among others [23][24][25]. There are a few successful reports on a rapid breeding program in apple by genetic modification of the flowering pathway [26][27][28]. A similar strategy can be used in breeding programs of Jatropha.…”
Section: Discussionmentioning
confidence: 99%
“…Flower initiation has been intensively studied in Arabidopsis, and orthologs/homologs of genes for LFY, AP1, and TFL1 have been cloned from apple trees among others [23][24][25]. There are a few successful reports on a rapid breeding program in apple by genetic modification of the flowering pathway [26][27][28]. A similar strategy can be used in breeding programs of Jatropha.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of the molecular mechanisms of tree aging, many age-related genes have been identified (Busov et al 2004;Carlsbecker et al 2004;Diego et al 2004;Fernández-Ocaña et al 2010;García-López et al 2014;Hutchison et al 1990;Li et al 2010Xu et al 2016;Zhang et al 2016), such as miR156 (Wang et al 2011b) and Flowering Locus T (Böhlenius et al 2006;Hsu et al 2006Hsu et al , 2011, and some have been used to change the agronomic traits of plants (Flachowsky et al 2012;Kotoda et al 2006;Li et al 2013a;Yamagishi et al 2014). Larix kaempferi is a forest tree of important ecological and economic value, widely grown in the Northern Hemisphere, but its genome has not been sequenced.…”
Section: Communicated By F Gugerlimentioning
confidence: 99%
“…TERMINAL FLOWER1 (TFL1) is in the same gene family as FT, but TFL1 (and homologs) acts as a competitive inhibitor of FT (Hanano and Goto, 2011;Ho and Weigel, 2014;Lifschitz et al, 2014). Consequently, either FT gain of function or TFL1 loss of function results in more determinate growth and faster transition to reproductive growth (Flachowsky et al, 2012;Freiman et al, 2012). Other genes in the flowering pathway are used similarly as breeding tools to accelerate flowering; for example, apple transformed with a flowering-associated MADS box gene from silver birch (Betula spp.…”
Section: How Can Breeding Be Accelerated?mentioning
confidence: 99%